2002
DOI: 10.1063/1.1490599
|View full text |Cite
|
Sign up to set email alerts
|

NO angular distributions in the photodissociation of (NO)2 at 213 nm: Deviations from axial recoil

Abstract: Angular distributions of selected rotational states of NO(A 2 ⌺ ϩ ,ϭ0) products obtained in the 213 nm photodissociation of (NO) 2 have been determined in a molecular beam by using the photofragment ion imaging technique. Specifically, images of NO(A,ϭ0) products in Nϭ0, 11, and 19 have been recorded, for which the maximum energies available to the NO(X 2 ⌸) products are 2038, 1774, and 1278 cm Ϫ1 , respectively. The recoil anisotropy parameter of the photofragments, ␤ eff , decreases significantly at low cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
(44 reference statements)
2
39
0
Order By: Relevance
“…These time scales were found to match for excitation wavelengths below 220 nm and indicated a lifetime contraction with decreasing pump wavelength. While an effective photodissociation lifetime additionally depends on the dimer Rydberg lifetime, these results corroborate photofragment imaging studies reported by Demyanenko et al 178 that find higher fragment anisotropy for higher excitation energies in this region, suggested to result from shortened dimer lifetimes.…”
Section: Neutral Photodissociation Dynamicssupporting
confidence: 80%
“…These time scales were found to match for excitation wavelengths below 220 nm and indicated a lifetime contraction with decreasing pump wavelength. While an effective photodissociation lifetime additionally depends on the dimer Rydberg lifetime, these results corroborate photofragment imaging studies reported by Demyanenko et al 178 that find higher fragment anisotropy for higher excitation energies in this region, suggested to result from shortened dimer lifetimes.…”
Section: Neutral Photodissociation Dynamicssupporting
confidence: 80%
“…The observed NO(A, 3s) product state distributions supported the notion of a planar dissociation involving restricted intramolecular vibrational energy redistribution (IVR) [176]. A scheme for studying NO dimer photodissociation dynamics via TRPES is depicted in Fig.…”
Section: E Photodissociation Dynamicsmentioning
confidence: 83%
“…Following photolysis, the dimer undergoes fast dissociation, and NO(A 2 ⌺ ϩ ,N) products are detected by resonance enhanced multiphoton ionization ͑REMPI͒ and velocity map ion imaging, providing velocity and angular distributions of state-selected products. The experiments are similar to those carried out at 213 nm, 12 and therefore, only procedures that have changed are discussed in detail.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study ͑Paper I͒, 12 we examined in detail the angular distributions obtained in the photodissociation of (NO) 2 at 213 nm (E † ϭ2038 cm Ϫ1 ) for specific NO(A) rotational states. Using the velocity map ion imaging technique, we obtained speed-dependent recoil anisotropy parameters ␤ eff from images of selected NO(A,N) states.…”
Section: Introductionmentioning
confidence: 99%